Social justice and protective discrimination policy in India - constitutional spirit and emerging realities - Kumar Suresh (2000)
The founding fathers of the Indian Constitution were quite aware about the dynamics of socio-economic order and the inegalitarian caste system. The protective discrimination policy was therefore, envisaged as means of delivering social justice and equalising opportunity structure. But during the last fifty years of the working of the constitutions the experiences of protective discrimination policy has been positive and negative. The policy has led to the emergence and expansion of middle class among the OBCs, SCs and STs also. The negative side of the policy is alarming. The benefits of the policy is not reaching up to the lowest level and poor sections of the target group. Intra and inter-caste differences have surfaced which, in its ultimate analysis defeats the spirit of the constitutions. Therefore, a reorientation of the policy is needed which should be more near to the poor and most backward among the target groups. Moreover, protective discrimination policy should not be relied upon as the whole some policy of Social Justice. A comprehensive policy needed in this regards. - Reproduced
Keywords: India - Constitution; Social justice - India; Social justice